2016
DOI: 10.1002/chem.201601622
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Enantioselective Synthesis, Crystal Structure, and Photophysical/Chiroptical Properties of Aza[10]helicenes

Abstract: The enantioselective synthesis of an aza[10]helicene, possessing two pyridone units, has been achieved by the gold-catalyzed intramolecular quadruple hydroarylation of a tetrayne. This aza[10]helicene was successfully converted into a fully aromatic aza[10]helicene, possessing two pyridine units. Structure-photophysical and chiroptical properties relationship in a series of azahelicene isomers has also been disclosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 68 publications
1
26
0
1
Order By: Relevance
“…On the contrary, the optical rotation of 100e' (3182) was significantly larger than for 100i (1086). 134 Scheme 22. Synthesis of enantioenriched aza [6]ahelicenes 100a-e,f and bisaza [10]ahelicenes 100e' by enantioselective Au-catalyzed intramolecular hydroarylation and transformation of 100f to 100g.…”
Section: Other Cyclization Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the optical rotation of 100e' (3182) was significantly larger than for 100i (1086). 134 Scheme 22. Synthesis of enantioenriched aza [6]ahelicenes 100a-e,f and bisaza [10]ahelicenes 100e' by enantioselective Au-catalyzed intramolecular hydroarylation and transformation of 100f to 100g.…”
Section: Other Cyclization Processesmentioning
confidence: 99%
“…Synthesis of S-shaped double helicene 100h and 100i. 133,134 Table 8. Specific rotation values and photophysical data of enantioenriched azahelicenes 100a-i.…”
Section: Other Cyclization Processesmentioning
confidence: 99%
“…Surprisingly, the synthesis of large NGs using Au-catalysis is rare but has been successfully employed for alkyne benzannulations to afford various small NGs, including chiral helicene-like compounds [104], pyrenes [71,72,84], and phenanthrenes [69,75,76].…”
Section: Acid-mediated Alkyne Benzannulationsmentioning
confidence: 99%
“…Therefore, their asymmetric synthesis is a highly important target in organic synthesis [3] . However, there are very few examples of the enantioselective synthesis of azahelicenes and azahelicene‐like molecules, [3a–c] in contrast to the large number of examples reported in the enantioselective synthesis of carbohelicene and carbohelicene‐like molecules [4,5] . In 2012, List achieved the enantioselective synthesis of azahelicenes including diaza[8]helicene A by the organocatalyzed annulation (Figure 1a) [3a] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, List achieved the enantioselective synthesis of azahelicenes including diaza[8]helicene A by the organocatalyzed annulation (Figure 1a) [3a] . Subsequently, our research group reported the enantioselective synthesis of aza[6]helicenes B by the gold(I)‐catalyzed intramolecular hydroarylation of alkynes (Figure 1a) [3b,c] . The most widely used method for the enantioselective synthesis of carbohelicenes is the transition‐metal‐catalyzed [2+2+2] cycloaddition [4,6] .…”
Section: Introductionmentioning
confidence: 99%